Tuesday, 2 July 2013

2 July 2013 Lesson Summary - Wee Chang Han, (20)

Linear Law

To convert an equation to linear form, namely Y = mX + c.


Replacing the value of the y-axis and x-axis with the Y and the X value will result in a linear graph. This would simplify the graph and allows us to discover the relationship between the more variables more quickly and efficiently.

EG: y = ab^x

convert to Y = mX + c format

lg both sides:

lg y = lg a + x lg b

Convert to form Y = mX + c

lg y (Y) = x (X) lg b(m) + (lg a)

Full explanation inclusive of graph and conversion to Y = mX + c.
Mr Johari's Workings on the Whiteboard

No comments:

Post a Comment